The CORBA connector model. - Robert, Sylvain (Software engineering notes.)
Embedded systems designers are more than ever confronted with issues related to complexity management. New design methods have emerged that could help to face this rising concern, but they do not yet satisfy all specific requirements from this application domain. In this scope, we aim to adapt the CORBA Component Model approach to embedded software design. This adaptation notably requires reworking the CCM interaction support, in order to provide more flexibility and extensibility. We think that this objective can be reached by integrating connectors in the CCM. This paper describes the benefits of this approach, and outlines the modifications we have made to the CCM in order to integrate connectors.